2022
DOI: 10.1002/jcla.24234
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and prognostic value of serum Chitinase 3‐like protein 1 in hepatocellular carcinoma

Abstract: The serum Chitinase 3‐like protein 1 (CHI3L1) protein level can distinguish the stages of liver fibrosis to a great extent. However, the diagnostic and prognostic significance of serum CHI3L1 in hepatocellular carcinoma (HCC) is not clarified. To evaluate the diagnostic and prognostic value of CHI3L1 in HCC, a total of 128 HCC patients treated in the HwaMei Hospital, University of Chinese Academy of Sciences, from December 2018 to April 2020 were collected retrospectively. Matched age and gender subjects, 40 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…As an unfavorable gene involved in ACAFRGs, CHI3L1 was highly expressed in gene cluster A and the high-aging CAF score group ( Figure 3K , Figure 4H ). Consistent with our results, CHI3L1 has been reported to be associated with poor prognosis in hepatocellular carcinoma ( Wang et al, 2022 ). A recent study showed that CHI3L1 was significantly correlated with severe state and adverse prognosis for COVID-19 patients ( Kimura et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…As an unfavorable gene involved in ACAFRGs, CHI3L1 was highly expressed in gene cluster A and the high-aging CAF score group ( Figure 3K , Figure 4H ). Consistent with our results, CHI3L1 has been reported to be associated with poor prognosis in hepatocellular carcinoma ( Wang et al, 2022 ). A recent study showed that CHI3L1 was significantly correlated with severe state and adverse prognosis for COVID-19 patients ( Kimura et al, 2021 ).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, it is necessary to further explore CHI3L1 for the diagnosis of liver fibrosis, including large-scale and multicenter studies, multifactor analysis, and the combined application of multiple indicators or methods. CHI3L1 can be used as a biomarker for prognostic assessment and targeted therapy in liver diseases [ 27 , 28 ], which also needs to be validated by using the CLIA. Considering the important clinical value of CHI3L1 in other diseases [ 3 ], the developed CLIA will be a powerful tool to further explore the clinical relevance of CHI3L1.…”
Section: Discussionmentioning
confidence: 99%
“…CHI3L1 is a non-enzymatic protein of the glycoside hydrolase family 18 that binds chitin. Many studies have shown a strong correlation between CHI3L1 and stages and outcomes of numerous cancers [28][29][30]. CHI3L1 has been reported to promote cancer cells growth, proliferation and metastasis but also angiogenesis, vasculogenic mimicry and tumor associated inflammation [31].…”
Section: Discussionmentioning
confidence: 99%